Deep Trephination Allows High Rates of Successful Pneumatic Dissection for DALK Independent of Surgical Experience. Issue 5 (May 2019) - Myerscough, James; Bovone, Cristina; Scorcia, Vincenzo; Ricci-Filipovic, Benedetta; Leon, Pia; Mimouni, Michael; Nahum, Yoav; Busin, Massimo
Abstract : Purpose: To evaluate the relationship between surgical experience and the success rate of pneumatic dissection for deep anterior lamellar keratoplasty (DALK) using deep trephination. Methods: A noncomparative case series evaluating the first 10 consecutive keratoconic eyes without deep stromal scarring, operated by 8 surgeons of 3 different experience levels, was conducted; there were a total of 80 patients. Standardized DALK was performed, including deep trephination 450 to 550 μm in depth and 9 mm in diameter, pneumatic dissection, removal of the stroma, and transplantation of a 9-mm partial-thickness anterior lamellar graft. The success rate of pneumatic dissection correlated with surgical experience. Results: Pneumatic dissection succeeded in 7, 7, 8, and 9 cases of 10 cases in the first group of 4 inexperienced surgeons (under 10 previous keratoplasties of any kind); in 9 and 10 of 10 cases in the second group of 2 relatively experienced surgeons (under 100 keratoplasties); and in 10 and 8 of 10 cases in the third group of 2 very experienced surgeons (more than 1000 previous keratoplasties). No difference between the groups was found to be statistically significant with the χ 2 test ( P > 0.05). Conclusions: The standardized DALK technique using a deep trephination allows high success rates of pneumatic dissection even for surgeons inexperienced in keratoplasty.